The relationship between coronary slow flow phenomenon and urotensin-II: A prospective and controlled study - Zengin, Halit (Anatol J Cardiol, 2015)
OBJECTIVE: The underlying mechanism of coronary slow flow (CSF) has not yet been clarified, although many studies have been conducted to understand its pathophysiology. In this study, we investigated the role of a very potent vasoconstrictor, urotensin-II (UII), in the pathophysiology of CSF. This prospective and controlled investigation aimed to evaluate the association between CSF and serum levels of UII. METHODS: Our study included 32 patients with slow flow in any coronary artery and 32 patients with normal coronary arteries. Coronary flow was calculated using the Thrombolysis in Myocardial Infarction (TIMI) frame count (TFC) method, and CSF was defined as TFC ≥39 for the left anterior descending artery, TFC ≥27 for the circumflex coronary artery, and TFC ≥24 for the right coronary artery. UII levels in blood samples obtained from both groups were measured by enzyme-linked immunosorbent assay (ELISA) method. RESULTS: UII levels were significantly higher in the CSF group than in the control group [122 pg/mL (71-831), 95 pg/mL (21-635), respectively; p<0.001]. High-density lipoprotein (HDL) levels were lower in the CSF group, and leukocyte counts were significantly higher. A positive correlation between UII and mean TFC (r=0.524, p=0.002) was found in the CSF group. The multivariate logistic regression analysis determined that UII, HDL, and cigarette smoking were independent indicators in predicting CSF (OR=1.010, 95% confidence interval 1.002-1014, p=0.019; OR=0.927, 95% confidence interval 0.869-0.988, p=0.019; OR=5.755, 95% confidence interval 1.272-26.041, p=0.021, respectively). CONCLUSION: Serum UII levels were found to be significantly higher in the CSF group, suggesting that UII may be one of the underlying factors in the pathogenesis of CSF